Efektivitas BUMDES dalam Pemberdayaan Masyarakat Desa di Desa Wisata Paksebali Kecamatan Dawan Kabupaten Klungkung - Dewata, Begawan Raka; Sastra Wijaya, Komang Adi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Paksebali Tourism Village is designated as a tourist village area based on Regulations of Regent of Klungkung No. 2 of 2017. BUMDES (Village-Owned Enterprises) Paksebali is an institution whose task is to develop all the potential of the village. The purpose of this study is to see the extent to which the effectiveness of the BUMDES Paksebali in the process of community empowerment develops the Paksebali tourism village in accordance with the stated goals and plans. Measurement of effectiveness uses the Masruci theory with 3 variables that affect the level of effectiveness of an organization with a source-based approach, an approach based on a process and approach based on goals. The results of this study indicate that there are still shortcomings implemented by BUMDES in community empowerment, one of which is in the recruitment process and the lack of facilities used by the community when working on BUMDES units. Keywords: Effectiveness, BUMDES (Village-Owned Enterprises), Empowerment, Tourism Village